Modafinil Induced Psychosis in a Patient with Bipolar 1 Depression - DiSciullo, Alexander A.; English, Clayton D.; Horn, William T. (Case Reports in Psychiatry, 2018)
Modafinil has been used as an adjunctive medication in the treatment of bipolar 1 depression with reported success. Case reports have been published demonstrating modafinil induced mania in bipolar patients and modafinil induced psychosis in schizophrenic patients. To our knowledge, we report the only case of modafinil induced psychosis in a patient with bipolar depression treated with both mood stabilizers and antipsychotics. In addition, it is the quickest onset to psychosis (2 days) at the lowest dosage of modafinil (100 mg/day) reported in the literature. Although favorable outcomes using modafinil for treatment of bipolar depression have been reported in literature, clinicians should remain cautious of the potential to rapidly induce psychosis with modafinil at low dosages in patients with bipolar depression despite being treated with mood stabilizers and antipsychotics.